NEMIPTERUS MESOPRION (SLEEKER 1853) (NEMIiPTERIDAE PISCES) A NEW RECORD FROM THE SEAS AROUND INDIA - Murty, V Sriramachandra (Indian Journal of Fisheries, 2011)
Neinipterus inesoprion (Bleeker) is reported for the first time from the Indian seas. This species resembles N. japonictis (Bloch) closely but differs from it in eolour, snout length, head length, height of suborbital bone and pelvic fin length. A description of the species is presented